2014
DOI: 10.15835/nsb649471
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Biological Properties of Burnet Weed (<i>Sanguisorba</i> spp.): A Review

Abstract: Great burnet (Sanguisorba officinalis L.) and small burnet (Sansguisorba minor Scop.) are edible, perennial weeds widely distributed in the world. These are the most widespread Sanguisorba species. The bioactive components of Sanguisorba plants include phenolics (phenolic acids, flavonoids and neolignans) and terpenoids. Large potential exists to use burnets as medicinal plants. Sanguisorba species are known to show anticancer properties, antioxidative, antimicrobial and antiviral activities. Also, Sanguisorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…1 The species is widely distributed throughout Europe and is commonly found in dry and semi-dry grasslands of the Mediterranean basin. 2,3 S. minor and other species of this genus (e.g. S. officinalis) are commonly used as medicinal species, while they are also edible and their young shoots and leaves are usually used in mixed vegetable salads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The species is widely distributed throughout Europe and is commonly found in dry and semi-dry grasslands of the Mediterranean basin. 2,3 S. minor and other species of this genus (e.g. S. officinalis) are commonly used as medicinal species, while they are also edible and their young shoots and leaves are usually used in mixed vegetable salads.…”
Section: Introductionmentioning
confidence: 99%
“…S. officinalis) are commonly used as medicinal species, while they are also edible and their young shoots and leaves are usually used in mixed vegetable salads. 2,4,5 Plants grown in the wild are also used as forage species due to their high nutritional value, dry matter digestibility and metabolizable energy. 6 Sanguisorba species are rich sources of secondary metabolites with significant bioactive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that Sanguisorba spp. extracts inhibit AChE activity and the glycogen synthase kinase 3β (GSK3) (19,20). Both of these enzymes have important roles in AD (21).…”
Section: Introductionmentioning
confidence: 99%
“…Sanguisorba officinalis L. is a member of the Rosaceae family and is a widely distributed perennial weed worldwide [ 9 ]. Edible dried roots of S. officinalis L. (known as JiYu in Korea and Japan or DiYu in China) have been used as a herbal medicine for centuries.…”
Section: Introductionmentioning
confidence: 99%